2019
DOI: 10.1111/oik.05874
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization drives unique latitudinal patterns of insect herbivory and tree condition

Abstract: Urban landscapes are characterized by high proportions of impervious surface resulting in higher temperatures than adjacent natural landscapes. In some cities, like those at cooler latitudes, trees may benefit from warmer urban temperatures, but trees in many cities are beset with problems like drought stress and increased herbivory. What drives patterns of urban tree health across urbanization and latitudinal temperature gradients? In natural systems, latitude–herbivory relationships are well‐studied, and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 72 publications
2
11
1
Order By: Relevance
“…These scale species develop invasive traits, proliferate, and become chronic urban tree pests due to the UHI effect [49][50][51]. Other scale species on the same trees under the same conditions do not display invasive phenotypes or become pests [52,53]. Melanaspis tenebricosa and P. quercifex are consistent with characterizations of sleeper species as they are innocuous native species that become pests with environmental change, here, the UHI effect.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…These scale species develop invasive traits, proliferate, and become chronic urban tree pests due to the UHI effect [49][50][51]. Other scale species on the same trees under the same conditions do not display invasive phenotypes or become pests [52,53]. Melanaspis tenebricosa and P. quercifex are consistent with characterizations of sleeper species as they are innocuous native species that become pests with environmental change, here, the UHI effect.…”
supporting
confidence: 55%
“…The strongest path indicated that impervious surface cover increased temperature which, in turn, increased scale density. Subsequent research on urban red maples corroborated these results [53,56,61,87].…”
Section: Gloomy Scale and Red Maplesmentioning
confidence: 69%
“…Although latitude can be a useful integrator of several axes of global variation in climate, relatively few studies investigate the hypothesized underlying climatic drivers behind latitudinal patterns in herbivory (e.g., Adams & Zhang, 2009;Gao et al, 2019;Moreira et al, 2015;Zhang, Zhang, & Ma, 2016), while even fewer consider nutrient availability that can have different spatial patterns than climate variables (e.g., Lynn & Fridley, 2019;Moreira, Castagneryrol, Abdala-Roberts, & Berny-Mier y Teran JC, Timmermans BGH, Bruun HH, Covelo, F, Glauser G, Rasmann S, Tack AJM., 2018). In addition, it is possible that latitudinal variation in insect herbivore damage and plant resistance to herbivory are driven by resource availability, trade-offs in plant growth and defenses (Kim, 2014), and that they depend on herbivore specialization (Dyer & Forister, 2019), as well as land use or urbanization (Just, Dale, Long, & Frank, 2019). Though climate is surely a strong driver of latitudinal variation in herbivory, deviations from this expected pattern are likely due to unmeasured edaphic and plant-trait controls on consumption rates.…”
mentioning
confidence: 99%
“…The former mainly links to the socio-economic dimension of urbanization and the latter focuses more on urban biophysical and environmental factors. These two kinds of indices are more straightforward and easily obtained from urban census data or retrieved from remotely sensed data, which have been widely utilized to study urbanization and their relationships to, or impacts on urban biodiversity [72,[100][101][102][103]. Compared with most of the previous studies, our study directly used the urban land use proportion to quantify the urbanization degree and established a quantitative relationship to plant species diversity that can help easily understand and predict the influences of urbanization on plant diversity; therefore, this study can provide insight to optimize ecosystem services in future urban green space planning and design [104][105][106].…”
Section: The Impacts Of Urbanization On Plant Diversitymentioning
confidence: 99%